Nexus of climate change adaptation and household wealth in climate risk hotspots – Insights from rural farm households of Pakistan - Shangao Wang; Panhwar Ghulam Mustafa; Gershom Endelani Mwalupaso; Zhou Li (Climate Risk Management)
The agricultural sector is a cornerstone of economic development, particularly in low-income countries where smallholder farming supports livelihoods and food security. However, the increasing unpredictability of climatic factors poses significant challenges, threatening its capacity to bolster smallholder farmers’ household wealth through food production. While climate adaptation measures have been widely promoted, there remains a notable lack of empirical evidence establishing the relationship between climate adaptation and household wealth. Addressing this critical research gap, this study examines the relationship between climate adaptation and household wealth among 400 wheat smallholder farmers in Sindh province, Pakistan. Using endogenous switching regression (ESR) and propensity score matching (PSM) for robustness, we estimate the average treatment effect on the treated (ATT). The results consistently show that climate adaptation significantly increases per capita household wealth, primarily through enhanced crop production. Counterfactual analysis reveals that non-adopting households could have reduced poverty severity by 15% and extreme poverty by 17% had they adopted adaptation measures. These findings provide compelling empirical evidence for policymakers to prioritize adaptation support frameworks—such as subsidized inputs or training programs—which are indispensable for safeguarding food production, reducing climate vulnerability, and lifting smallholders out of poverty. By demonstrating the dual benefits of adaptation—wealth accumulation and poverty alleviation—this study underscores the urgency of scaling up climate-resilient agricultural practices as a key strategy for reducing vulnerability and fostering sustainable livelihoods.